2013
DOI: 10.1136/bcr-2012-007968
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis-associated aplastic anaemia: a poor prognosis

Abstract: SUMMARYA 13-year-old boy presented with spontaneous skin and mucosal bleeds 3 weeks after acute hepatitis of unknown aetiology. Laboratory analyses revealed pancytopenia and bone marrow biopsy that confirmed the diagnosis of aplastic anaemia. Other causes of congenital and acquired aplastic anaemia were excluded. He was diagnosed with hepatitis-associated aplastic anaemia. He developed a critical clinical condition, becoming totally dependent on erythrocyte and platelet transfusions, and severe neutropenia, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Patients with HAAA develop severe pancytopenia weeks to months after an acute episode of self-relief hepatitis. The mean survival time after developing severe bone marrow aplasia is 2 months, and the fatality rate ranges from 78% to 88% ( 10 ). The treatment options for HAAA are IST and allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HAAA develop severe pancytopenia weeks to months after an acute episode of self-relief hepatitis. The mean survival time after developing severe bone marrow aplasia is 2 months, and the fatality rate ranges from 78% to 88% ( 10 ). The treatment options for HAAA are IST and allogeneic HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…A BM failure can be rapid and severe and is usually fatal if untreated. The mean survival time after developing severe BM aplasia is 2 months, and the fatality rate ranges from 78% to 88% 8 . The pathogenesis of HAAA remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the expansion of a liver-infiltrating cytotoxic T lymphocyte clone takes part in the development of HAAA, especially CD8 + cells might be important mediators of HAAA. Immunosuppressive therapy such as antithymocyte globulin (ATG) and cyclosporine has been reported to be effective, without eliciting any acute side effects 8 , 15 .…”
Section: Discussionmentioning
confidence: 99%
“…36,38 However, an earlier onset is not uncommon in literature, and patients can still have laboratory features of acute hepatitis on presentation with HAAA. 42 In fact, according to a study in bone marrow transplant patients by Safadi et al, around 40% of patients who develop HAAA still have the laboratory markers of hepatitis on diagnosis. 41 At the opposite extreme, HAAA can also be observed in 10% of patients after more than 1 year from a hepatitis episode.…”
Section: Aplastic Anemiamentioning
confidence: 99%
“…Cyclosporine and antithymocyte immunoglobulin (ATG) are the treatments of choice. 37,42 Cases of simultaneous improvement of hepatitis features and pancytopenia after the initiation of immunosuppressive treatment imply that the exact immune-mediated mechanism can be responsible for both hepatic and bone marrow injury. 37 Clinical data seem to confirm that, compared with the general population of patients with AA, patients with HAAA have similarly favorable results of bone marrow transplantation and immunosuppressive therapy.…”
Section: Aplastic Anemiamentioning
confidence: 99%